Analysis of Students' Learning Difficulties in Thematic Learning of Grade 2 Students of SD Negeri 2 Sucen Temanggung - Maelani Tyas Wahyuni; Amirul Mukminin (Journal of Educational Sciences, 2026)
Thematic learning in elementary school requires active student participation to achieve optimal learning outcomes. However, several second-grade students at SDN 02 Sucen still experience learning difficulties that hinder their participation in classroom activities. This study aims to identify the forms of students’ learning difficulties, the factors influencing them, and the efforts made by teachers and parents to address these issues. This research employed a qualitative descriptive design. The subjects consisted of one second-grade teacher, three students with learning difficulties, and three parents. Data were collected through classroom observations, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing/verification. The findings indicate that students’ learning difficulties are characterized by low understanding of learning materials, lack of concentration during learning activities, and slow task completion. These difficulties are influenced by internal factors such as motivation and basic academic abilities, as well as external factors including the learning environment and parental guidance patterns. In conclusion, students’ learning difficulties in thematic learning require integrated interventions through adaptive teaching strategies by teachers and consistent learning support from parents.